Autonomy in Jewish philosophy - Seeskin, Kenneth, 1947- (Cambridge University Press, 2001)
"Autonomy in Jewish Philosophy examines an important theme in Jewish thought from the Book of Genesis to the present day. Although it is customary to view Judaism as a legalistic faith leaving little room for free thought or individual expression, Kenneth Seeskin argues that that view is wrong. Where some see the essence of the religion as strict obedience to divine commands, Seeskin claims that God does not just command but forms a partnership with humans requiring the consent of both parties. Looking at classic texts from Biblical, Rabbinic, and philosophical literature, Seeskin shows that Judaism has always respected freedom of conscience and assigned an important role to the power of human reason. The book both considers existing arguments and presents new ideas about the role of autonomy in Judaism. Clear and concise, it offers a refreshing alternative to the mysticism and dogmatism prevalent in much of the recent literature."--Jacket